Hands-on machine learning with Scikit-Learn and TensorFlow concepts, tools, and techniques to build intelligent systems - Géron, Aurélien (O'Reilly Media, 2017)
Through a series of recent breakthroughs, deep learning has boosted the entire field of machine learning. Now, even programmers who know close to nothing about this technology can use simple, efficient tools to implement programs capable of learning from data. This practical book shows you how. By using concrete examples, minimal theory, and two production-ready Python frameworks--scikit-learn and TensorFlow--author Aurélien Géron helps you gain an intuitive understanding of the concepts and tools for building intelligent systems. You'll learn a range of techniques, starting with simple linear regression and progressing to deep neural networks. With exercises in each chapter to help you apply what you've learned, all you need is programming experience to get started.
Includes index. - Online resource; title from title page (Safari, viewed March 22, 2017)
Keywords: Machine learning; Python (Computer program language); Apprentissage automatique; Python (Langage de programmation); COMPUTERS; Cybernetics; COMPUTERS; Machine Theory